2020
DOI: 10.3390/jcm9040985
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Supported Self-Management in Community-Based Stroke Care: A Secondary Analysis of Nurses’ Perspectives

Abstract: The provision of supported self-management (SSM) is recommended in contemporary guidelines to address the longer-term needs and outcomes of stroke survivors and their families, yet its implementation across stroke pathways has been inconsistent. This paper presents a secondary analysis of qualitative data, which aims to identify and offer insight into the challenges of implementing SSM from the perspectives of community stroke nurses (n = 14). The findings revealed that the implementation of SSM in stroke is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…It is noted that most stroke patients have at least one modifiable risk factor, such as diabetes, smoking, obesity, physical inactivity, and an unhealthy diet that is often poorly managed during the follow-up process (Bridgwood et al, 2018). Self-management support is a significant strategy in the prevention of recurrent stroke (Kidd et al, 2020). As a result of a meta-analysis study, it was found that self-management interventions were effective in improving overall risk factor control in stroke patients (Sakakibara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that most stroke patients have at least one modifiable risk factor, such as diabetes, smoking, obesity, physical inactivity, and an unhealthy diet that is often poorly managed during the follow-up process (Bridgwood et al, 2018). Self-management support is a significant strategy in the prevention of recurrent stroke (Kidd et al, 2020). As a result of a meta-analysis study, it was found that self-management interventions were effective in improving overall risk factor control in stroke patients (Sakakibara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…30 The implementation of supported self-management may also be influenced by different perspectives on, and interpretations of, supported self-management in stroke. 26 Thus, although evidence suggests supported self-management in stroke is effective, to optimise and meaningfully tailor its delivery to stroke survivors' needs in the community, we need to learn more about how supported self-management works and how it is delivered in different settings of community rehabilitation. The proposed realist evaluation study aims to address this gap.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Several well-defined supported self-management interventions in stroke exist, for example, Bridges25 in the UK and Take Charge in New Zealand 18 24. However, our previous research and anecdotal evidence suggests that the diffusion and delivery of supported self-management in practice requires organisational culture change within the healthcare system, rather than the simple implementation of a discrete and well-defined intervention with specific evaluation outcomes 20 25 26. Supported self-management approaches have often been delivered according to a set of principles or ideas that fit with, or are in some way influenced by, the system or organisational context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, approaches to proceed a self-management or home-based rehabilitation has a certain effect not only to maintain chronic health condition, but also to improve body function [ 3 , 4 ]. It is suggested that tailored counselling or with tailored supervised training as well as nurses’ intervention improves participation and arm function [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%